A STUDY ON THE IMPORTANCE OF BLACK SWANS AND VAR (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2021)
There are two general classes of likelihood spaces;  each is unmistakable, both subjectively and  quantitatively. The principal appropriation is  known as thin tail, the second is fat tail. In slight  tail disseminations, factual special cases happen  yet they don’t convey bizarrely enormous results.  In fat-tail conveyances, when critical deviations  (Black swans) happen, the results are normally  disastrous in nature. Black Swan is an occasion or  event that strays past what is regularly expected  of a circumstance and that would be very hard to  anticipate. Standard deviation is a helpful factual  estimation of hazard, if the fundamental resource  returns are circulated in a typical manner about  the mean. Be that as it may, if the benefit returns  go amiss altogether from what might be normal  in a slim tail standard deviation is regularly a  lacking and poor estimation of all out hazard  and can frequently bring about the genuine  underestimation of potential misfortunes.  VaR is genuinely exact in anticipating little  day by day misfortunes with high likelihood;  it separates totally in determining enormous  calamitous misfortunes that exist in the tail of  the dispersion – Black swan occasions.
Keywords: VaR; Black Swans; Thin Tail; kurtosis; fat tails